Direct Z-Scheme NiWO4/CdS nanosheets-on-nanorods nanoheterostructure for efficient visible-light-driven H2 generation. (26th February 2022) - Yin, Xing-Liang; Li, Lei-Lei; Gao, Gai-Mei; Lu, Yao; Shang, Qian-Qian; Zhao, Hai-Tao; Li, Da-Cheng; Dou, Jian-Min
Abstract: Exploiting efficient catalysts is of interest for solar-driven water splitting. Herein, a novel NiWO4 /CdS nanosheets-on-nanorods direct Z-Scheme heterostructure was developed by using a facile in-situ approach. The optimized NiWO4 /CdS heterostructure shows a H2 evolution rate of 26.43 mmol g −1  h −1 exceeding that of bare CdS by more than 75 folds. Systematic investigations reveal the nanostructures with numerous active sites, intimate contact interface, and enhanced charge separation rate synergistically account for the outstanding performance of the NiWO4 /CdS. Moreover, the band structures were detailedly analyzed and the tentative photocatalytic mechanism was proposed, which could contribute to deeply understanding the catalytic process and guide the synthesis of the efficient heterostructure. These findings and strategies may have great significance in promoting the development of highly efficient and low-cost photocatalysts. Graphical abstract: Image 1 Highlights: A novel NiWO4 /CdS Z-scheme heterostructure was first constructed by using a facile approach. The NiWO4 /CdS exhibits a H2 evolution rate of 26.43 mmol g −1  h −1 far acceding that of CdS. The good performance was attributed to the formation of the well-defined heterostructure. The band energy level and photocatalytic mechanism were detailedly investigated.